2016
DOI: 10.3747/co.23.3161
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Illness for Metastatic Melanoma in Canada, 2011–2013

Abstract: Background Detailed epidemiology for patients with advanced metastatic melanoma in Canada is not well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…6,7,33,34,[37][38][39][40][41][42] Several studies have significantly contributed to the understanding of the epidemiology and risk factors for CMM in Canada. 9,14,16,18,28,[43][44][45][46][47][48][49][50][51][52][53][54] We recently reported an extensive analysis of CMM epidemiology in Canada from 1992 to 2010 and highlighted a steady increase in the incidence and mortality of this malignancy in both sexes within the aforementioned time period. 55 Briefly, the most commonly reported specific subtype of CMM in the Canadian population was superficial spreading melanoma, which comprised 37.4% of all CMM cases.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,33,34,[37][38][39][40][41][42] Several studies have significantly contributed to the understanding of the epidemiology and risk factors for CMM in Canada. 9,14,16,18,28,[43][44][45][46][47][48][49][50][51][52][53][54] We recently reported an extensive analysis of CMM epidemiology in Canada from 1992 to 2010 and highlighted a steady increase in the incidence and mortality of this malignancy in both sexes within the aforementioned time period. 55 Briefly, the most commonly reported specific subtype of CMM in the Canadian population was superficial spreading melanoma, which comprised 37.4% of all CMM cases.…”
Section: Introductionmentioning
confidence: 99%
“…The data showed that the pathologic T stage continued to be in uencing factors of the prognosis of MM patients in TCGA, with p-values of 0.025. For every MM patient, a PI as a risk score was calculated according to equation (1). The PI was signi cantly associated with OBS in metastasis group.…”
Section: Establishment Of the Immune-related Genes Risk Signaturementioning
confidence: 99%
“…Its incidence has increased faster than that of any other cancer over the past half-century and the annual costs of treatment in the United States alone have risen rapidly. The average 5-year survival rate is approximately 90, 70, 40, and less than 10% for patients with stage I, II, III, and IV malignant melanoma, respectively [1][2][3][4]. One of the standard methods of diagnosing and treating melanoma is represented by surgical resection (melanoma is frequently located in the skin, so excision is still widely applied at present for patients with early-stage melanoma due to its facile accessibility).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of melanoma are diagnosed at an early stage, which has been attributed to increased awareness of the malignancy [ 9 ]. At this stage, surgical excision may be curative [ 10 ]. However, a small proportion of patients have metastatic disease at presentation, and some develop metastases after their initial definitive treatment [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%